Application of Path Analysis to Determine the Effect of Self-Efficacy and The Role of Teachers on Work Readiness of Vocational High School Students Through Industrial Work Practice Experience (Journal of Applied Statistics and Data Science, 2025)
Path analysis is one of the statistical methods that is a further development of regression analysis. Path analysis aims to determine the direct and indirect effects of a variable on other variables. Vocational High Schools (SMK) are educational institutions that prepare students to enter the world of work. Therefore, SMK aims to encourage the development of students' learning skills, both in terms of knowledge, skills, and attitudes to support the development of their potential. The purpose of this study was to determine the effect of self-efficacy and the role of teachers on the work readiness of vocational students through industrial work practice experience. Data were obtained through distributing questionnaires with a Likert scale. The population in this study were students of SMK Islam Donomulyo grade XII in the 2022/2023 school year while the sample in this study were students of SMK Islam Donomulyo grade XII who had carried out industrial work practices. The results showed that the variables of self-efficacy and the role of the teacher had a significant effect on the variable of student work readiness through industrial work practice experience and the variable that had the greatest effect was the role of the teacher on student work readiness through industrial work practice experience.